Ripple down rule based decision intelligence for mental disorder diagnosis - Rahman, G.M. Arafat; Ibnul, Tahmid Nizam; Mia, MD. Shamim; Akash, Abid Mahmood; Banerjee, Avinandan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.